Question

Asked Jan 26, 2020

1 views

Find gof and fog, if f : R → R and g : R → R are given by f(x) = cos x

and g (x) = 3x^{2}. Show that gof ≠ fog.

Step 1

Given, f : R → R and g : R → R are given by f(x) = cos x and g (x) = 3x^{2}

Step 2

Now,

Step 3

And

...Find answers to questions asked by student like you

Show more Q&A

Q: how many miles will a person run during a 10-kilometer race?

A: Click to see the answer

Q: Find the inverse of the following function: f(x) = −2 log 2(x − 1) + 2

A: Plug f(x)=y

Q: When 4 is added to two numbers, the ratio is 5:6. When 4 is subtracted from the two numbers, the rat...

A: Let the numbers are x and y.When 4 is added to two numbers, the ratio is 5:6.That can be written usi...

Q: Explain Equality of matrices. Give a suitable example.

A: Equality of matrices:Two matrices are equal if all three conditions given below are satisfied: · Bot...

Q: Solve the equation : 5(- 3x - 2) - (x - 3) = -4(4x + 5) + 13

A: The given equation is,

Q: Let R be the relation in the set {1, 2, 3, 4} given by R = {(1, 2), (2, 2), (1, 1), (4,4),(1, 3), (3...

A: The given set and the relation R is shown below.

Q: A ball is shot straight upward, with its height, in feet, after t seconds given by the function f (t...

A: A ball is shot straight upward, with its height, in feet, after t seconds given by the function f (t...

Q: Teachers divided students into groups of 3. Each group of 3 wrote a report that had 9 pictures in it...

A: Click to see the answer

Q: Show that the function f : R → R,defined as f(x) = x2 , is neither one-one nor onto.

A: We will show this by counter examples.Let x= 2 and -2 Then f(2)= 2^2 = 4 and f(-2)= (-2)^2 = 4 This ...